Do community factors matter? An analysis of the achievement gap between indigenous and non-indigenous children in Peru. (March 2019) - Arteaga, Irma; Glewwe, Paul
Highlights: Expands the Blinder-Oaxaca decomposition to include community effects. Ethnic gap increases for math and vocabulary during the first years of school. Parental education and child's health explain most of the third-grade gap. Heterogeneity in community effects explain about half of the ethnic gap. Valuable information for policy makers; guide implementation of targeted policies. Abstract: In both the developed and developing world, the racial and ethnic test score gap is a vexing and persistent social problem. While the literature has focused on achievement gaps' underlying family and children determinants, in this article, we demonstrate how to expand the Blinder-Oaxaca decomposition to include community sorting effects and heterogeneity in community impact effects, factors that have not been considered before in achievement gap research. Using the 2001 cohort of the Young Lives Longitudinal Survey for Peru, our results show that at over the first four years of school, however, indigenous children lose substantial ground relative to non-indigenous children, increasing the average gap to 0.49 standard deviations (of the distribution of test scores) in math and 0.66 in vocabulary. Our findings suggest that parental education and child's health are important determinants of the gap for math and vocabulary; but also that the vocabulary gap is due in part to community effects. The pathways considered yield valuable information for policy makers who are interested in targeting policies to improve student learning among indigenous groups. These pathways are important for human capital formation and could potentially have longlasting impacts on educational attainment and poverty in Peru.